2015
DOI: 10.1139/cjfas-2013-0534
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale hydrogeomorphic influences on bull trout (Salvelinus confluentus) spawning habitat

Abstract: We investigated multiscale hydrogeomorphic influences on the distribution and abundance of bull trout (Salvelinus confluentus) spawning in snowmelt-dominated streams of the upper Flathead River basin, northwestern Montana. Within our study reaches, bull trout tended to spawn in the finest available gravel substrates. Analysis of the mobility of these substrates, based on one-dimensional hydraulic modeling and calculation of dimensionless shear stresses, indicated that bed materials in spawning reaches would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…; Bean et al . ). Also, our use of critical habitat, although necessary due to a lack of an alternative data source, was an imperfect proxy for actual rearing and spawning habitat for steelhead.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Bean et al . ). Also, our use of critical habitat, although necessary due to a lack of an alternative data source, was an imperfect proxy for actual rearing and spawning habitat for steelhead.…”
Section: Discussionmentioning
confidence: 97%
“…Construction and operation of these dams have dramatically altered spawning habitat, increased smolt and adult migration mortality, and contributed to significant declines in steelhead and salmon populations (Kareiva et al 2000). In addition, temperatures and flow are impacted by physical habitat characteristics and processes that are difficult to measure such as groundwater exchange that can moderate water temperature at low flows (Stanford et al 2005;Bean et al 2015). Also, our use of critical habitat, although necessary due to a lack of an alternative data source, was an imperfect proxy for actual rearing and spawning habitat for steelhead.…”
Section: Study Limitations and Future Directionsmentioning
confidence: 99%
“…Highly convergent areas, often found at lower elevations, will increasingly support isolated pockets of recruitment, thus acting as climate refugia buffering forests from climate change (Dobrowski, 2011;Mclaughlin et al, 2017). Here we build on research showing that abiotic diversity (topographic position and hydrologic routing) buffers ecosystem responses to hydraulic stress (Rodriguez-Iturbe et al, 2009;Bean et al, 2014;Wohl, 2017) and may mitigate some impacts of climate change.…”
Section: Hydraulic Stress Controls On Forest Distributionmentioning
confidence: 99%
“…Temperature data from the mouths of the two streams indicated that one is warmer than the other. While stream temperatures can differ from intragravel temperatures in redd sites, they provide a reasonable proxy (Bean et al ., ).…”
Section: Physical Habitat Characteristics For a Cool Stream (Downey Cmentioning
confidence: 97%